Living with the Beast: Wolves and Humans through Portuguese Literature. (2nd January 2016) - Lopes-Fernandes, Margarida; Soares, Filipa; Frazão-Moreira, Amélia; Queiroz, Ana Isabel
ABSTRACT: This paper explores representations of wolves in Portuguese literature using an anthropological framework to analyze perceptions, beliefs, knowledge, and practices. From a literary corpus compilation, 262 excerpts from 68 works that made reference to wolves were classified by grid analysis into 12 categories, encompassing the diversity of meanings attributed to these animals. Among wild carnivores, the wolf appears most frequently in the literary corpus analyzed. Most references concern conflict and economic losses caused by wolves' attacks, relating to a utilitarian view of the wild prevalent in rural communities. Nonetheless numerous excerpts reveal closeness with humans and the existence of an ecological knowledge. Writings from the early twentieth century express admiration for wolves and acknowledge their right to exist. Some focus on practices like organized hunts, bounties, or domestication attempts. The negative views depict the wolf as a scapegoat for the shortcomings of rural life. The human desire to control the wolf represents the conquest of the wild. The wolf in literature is the object of further symbolic attributions, associated with witchcraft, religion, specific beliefs and lore but also with freedom and the dark inner self of humans. Overall these mixed views express ambivalent feelings toward the species. The results of this case study demonstrate that humans have multiple views of wolves, views that are not necessarily polarized into negative or positive extremes but that coexist: the vermin and the noble beast. In rural communities the wolf is not viewed as a fragile animal needing protection or as a modern symbol of wilderness. This study is a contribution from anthropology to the understanding of the wolf's cultural dimensions and, by extension, human relationships with the natural world. We suggest that local knowledge and rural communities' perceptions of wolves should be integrated more effectively in conservation campaigns.